Hearing aid provision - can the limited obligation of statutory health insurance to provide indemnification only up to the reference price be successfully challenged in the social courts in cases of medical indication? - Lottner, Anna; Iro, Heinrich; Schützenberger, Anne; Hoppe, Ulrich (Laryngo-Rhino-Otologie, 2019)
OBJECTIVE: When patients are provided with hearing aids, the question may arise whether they are entitled to technically advanced and therefore more expensive hearing aids in cases of medical indication, or just to hearing aids for the reference price. This work provides an overview of decisions rendered by the German social courts. We investigated whether it is advisable for a patient to go to court if the statutory health insurance has disputed a claim, and how long the proceedings may take. MATERIAL AND METHODS: We looked for decisions in the commercial legal database "juris", using the search parameters "Hörgerät" (hearing aid) and "Zuzahlung" (additional payment). The reviewed decisions were issued between 2009 and 2019. RESULTS: A total of 97 relevant decisions were found. The results varied according to the specifics of the individual case. 63 % of the patients won their cases. The court procedures took between 0.3 years and 10.4 years. CONCLUSIONS: The study shows that it is uncertain whether the costs for hearing aids that exceed the reference price will be covered or reimbursed. As each case is in principle unique, the results vary. Nevertheless, taking legal action is recommended after thorough consideration in cases where statutory health insurances or other providers refuse to meet expenses incurred despite indication.
EVALuna2:209866